2018
DOI: 10.1021/acs.analchem.8b02426
|View full text |Cite
|
Sign up to set email alerts
|

A Dimethyl-Labeling-Based Strategy for Site-Specifically Quantitative Chemical Proteomics

Abstract: Activity-based protein profiling (ABPP) has emerged as a powerful functional chemoproteomic strategy which enables global profiling of proteome reactivity toward bioactive small molecules in complex biological and/or pathological processes. To quantify the degree of reactivity in a site-specific manner, an isotopic tandem orthogonal proteolysis (isoTOP)-ABPP strategy has been developed; however, the high cost and long workflow associated with the synthesis of isotopically labeled cleavable tags limit its wide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 32 publications
0
60
0
Order By: Relevance
“…The quantitative chemical proteomics was performed as recently described 42 peptides were also restricted to fully tryptic with a defined peptide false positive rate of 1%. The ratios (L/H) of reductive dimethylation were quantified by the CIMAGE software as described before 45 .…”
Section: Cys Reactivity Validation Through Iodoacetyl Modified Probe mentioning
confidence: 99%
“…The quantitative chemical proteomics was performed as recently described 42 peptides were also restricted to fully tryptic with a defined peptide false positive rate of 1%. The ratios (L/H) of reductive dimethylation were quantified by the CIMAGE software as described before 45 .…”
Section: Cys Reactivity Validation Through Iodoacetyl Modified Probe mentioning
confidence: 99%
“…Previous reports indicated that the application of multiplexed labeling strategies for cleavable linkers could result in the identification of several thousand unique peptides within a single experiment when using reductive dimethyl and iTRAQ labeling strategies 47,48 . We therefore decided to implement a recently published protocol 49 utilizing TMT labeling in combination with the DADPS linker (Supp Fig 3A).…”
Section: Resultsmentioning
confidence: 99%
“…To overcome the deficiencies in-gel separation and band identification, quantitative methods have been incorporated into chemical proteomics. 40,[115][116][117][118] By comparing the relative abundance of proteins between different samples or against appropriate negative controls, proteins with a higher abundance ratio (>1.5 or 2, different values have been used) than a threshold are identified as specific targets, thus avoiding nonspecific binders.…”
Section: Quantitative Proteomicsmentioning
confidence: 99%